Silent myocardial ischaemia in chronic stable angina: a study of its frequency and characteristics in 150 patients. Issue 5 (November 1988) - Mulcahy, D; Keegan, J; Crean, P; Quyyumi, A; Shapiro, L; Wright, C; Fox, K
Abstract : One hundred and fifty unselected patients with documented coronary artery disease were studied to establish the frequency and characteristics of silent myocardial ischaemia. Patients underwent ambulatory ST segment monitoring off all routine antianginal treatment (total 6264 hours) and exercise testing (n = 146). Ninety one patients (61%) had a total of 598 episodes of significant ST segment change, of which 446 (75%) were asymptomatic. Twenty seven patients (18%) had only painless episodes; 14 (9%) patients only painful episodes; 50 patients (33%) had both painless and painful episodes. The mean number of ST segment changes per day was 2.58 (1.95 silent); however, 11 patients (7%) had 50% of all silent episodes, and 48 patients (32%) had 91% of all silent episodes. Fifty nine patients (39%) had no ST segment changes on ambulatory monitoring, and 73 patients (49%) had no evidence of silent ischaemia. Episodes of silent ischaemia occurred with a similar circadian distribution to that of painful ischaemia, predominantly between 0730 and 1930. There was a similar mean rise in heart rate at the onset of both silent and painful episodes of ischaemia. Silent ischaemia was significantly more frequent in patients with three vessel disease than in those with single vessel disease, and was also significantly related to both time to 1 mm ST depression and maximal exercise duration on exercise testing. There was a highly significant relation between the mean number and duration of episodes of silent ischaemia in patients with positive exercise tests when compared with those with negative tests. No episode of ventricular tachycardia was recorded in association with silent ischaemic change.